High power coherent polarization locked laser diode - Phua, P. B. (2014)
We have coherently combined a broad area laser diode array to obtain high power single-lobed output by using coherent polarization locking. The single-lobed coherent beam is achieved by spatially combining four diode emitters using walk-off crystals and waveplates while their phases are passively locked via polarization discrimination. While our previous work focused on coherent polarization locking of diode in Gaussian beams, we demonstrate in this paper, the feasibility of the same polarization discrimination for locking multimode beams from broad area diode lasers. The resonator is designed to mitigate the loss from smile effect by using retro-reflection feedback in the cavity. In a 980 nm diode array, we produced 7.2 W coherent output with M2 of 1.5 x 11.5. The brightness of the diode is improved by more than an order of magnitude.